THE MEDIATING ROLE OF PSYCHOLOGICAL CONTRACT IN THE EFFECT OF SERVANT LEADERSHIP PERCEPTION ON EMPLOYEE VOICE - Zehir, Cemal; Burak, Emel (Kafkas University IIBF, 2025)
This study examines the mediating role of the psychological contract in the relationship between servant leadership perception and employee voice. The research focuses on employees in the Marmara Region, with 419 volunteers selected through convenience sampling due to time and resource constraints. A quantitative approach was used, and statistical analyses were conducted with IBM AMOS 24.0. Hypotheses developed from the literature were tested, contributing to theory and practice. Findings show that servant leadership perception and the psychological contract significantly impact employee voice. No significant relationship was found between servant leadership and the transactional contract, while a positive relationship was observed with the relational contract. Additionally, the relational contract partially mediates the relationship between servant leadership and employee voice, whereas the transactional contract has no significant mediating effect. The results were interpreted within the literature framework, and recommendations were provided.
Keywords: Servant leadership; psychological contract; employee voice; transactional contract; relational contract; FIT INDEX; BEHAVIOR; SILENCE; ANTECEDENTS; SPEAKING; MODELS; Business & Economics